2003
DOI: 10.1046/j.1462-5822.2003.t01-1-00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Redox-active metals in commercial preparations of lipopolysaccharide: implications for studies of cellular responses to bacterial products

Abstract: SummaryThe mechanisms by which lipopolyaccharide (LPS) activates cells have been the subject of intense investigation for many years. Whereas much information on this process has been collected for mammalian species, little is known about the signalling pathways operative in other animals. One general mode of cellular activation that has been recently proposed for pathways independent of the primary mammalian LPS receptor, CD14, involves reactive oxygen species (ROS) as intermediates in LPSinduced signalling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In addition, there were little or no observable NO production and the cells were MPO negative. Among the other phagocytic cell lines, RTS11 had neither respiratory burst nor NO production in response to stimulation, for SHK this is not described, while the cell lines, CLC and GMCL showed respiratory burst activity [1][2][3][4]52]. As bactericidal activity is lacking, low or not described, the bactericidal ability may not always or completely be linked to respiratory burst in such cells.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, there were little or no observable NO production and the cells were MPO negative. Among the other phagocytic cell lines, RTS11 had neither respiratory burst nor NO production in response to stimulation, for SHK this is not described, while the cell lines, CLC and GMCL showed respiratory burst activity [1][2][3][4]52]. As bactericidal activity is lacking, low or not described, the bactericidal ability may not always or completely be linked to respiratory burst in such cells.…”
Section: Discussionmentioning
confidence: 92%
“…Our results indicated that Fish are constantly exposed to microorganisms in the aquatic environment, many of which are bacterial pathogens (Vanamala et al, 2022). LPS is a heat-stable endotoxin derived from gramnegative bacteria that can mediate immune responses and extensively used to mimic bacterial infection in a number of fish species (Brubacher et al, 2003;Cavaillon, 2018;Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Fish are constantly exposed to microorganisms in the aquatic environment, many of which are bacterial pathogens (Vanamala et al, 2022). LPS is a heat‐stable endotoxin derived from gram‐negative bacteria that can mediate immune responses and extensively used to mimic bacterial infection in a number of fish species (Brubacher et al, 2003; Cavaillon, 2018; Lee et al, 2013). Administration of LPS in vivo has been demonstrated to affect reproductive processes in female rainbow trout by increasing apoptosis of ovarian follicle cells and by advancing the time of ovulation, resulting in a decrease in egg quality and embryonic survival (Crespo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional (2-D) gel electrophoresis of pulse-labeled proteins revealed a global analysis of protein synthesis and turnover in Escherichia coli (Weichart et al, 2003). Comparative proteomics of the human pathogen Campylobacter jejuni revealed an important first step in characterizing strain differences potentially responsible for different disease outcomes associated with this organism (Brubacher et al, 2003). Several studies subjected Mycobacterium tuberculosis to comprehensive proteomic analysis.…”
mentioning
confidence: 99%